Simulated and real train driving in a lineside automatic train protection (ATP) system environment. (December 2020) - Rosberg, Tomas; Thorslund, Birgitta
Abstract: This paper presents the differences between the train traffic simulation tool RailSys and real train traffic with focus on Electrical Multiple Units (EMU) and the Swedish automatic train protection (ATP) system ATC, on a single-track line. Braking, acceleration, different types of resistance and running times have been investigated. From this study it can be concluded that the margins to unconditional ATC braking is high with this specific ATC implementation and parameters, and that the braking differs depending on the signal target. Compared to RailSys with parameters settings according to Swedish Transport Administration recommendations, the measurements show significantly lower acceleration and deceleration, which results in differences between measured and simulated running time. Highlights: The margins to unconditional ATC braking are high. The braking differs depending on the signal target. Retardation towards stations without stop restrictions is >25% higher than retardation towards 40 km/h signalling points. The measurements show significantly lower acceleration and retardation compared to RailSys. Abstract : This is the first step exploring how capacity, signal systems, and driving behaviour interact and will be followed by investigations of the next generation signalling system ERTMS.